Religious beliefs and the utilization of traditional medicine among members of pentcostal churches in Emurin, Ogun state, Nigeria (2013)
"This study aims at determining the religious beliefs and the utilization of traditional medicine among members of Pentecostal Churches in Emure. The study was carried out using quota sampling technique. A semi containing 31 questions and an in used simultaneously to elicit information from church members. The researchhypothesized that there was a significant relationship between the use of traditional medicine and the sex of respondents. Also there exists a significant relationship between the denomination of respondents and the use of traditional medicine. Since p-value was greater than 0.05, both hypotheses were accepted. However it was discovered that 65.3% would opt for divine healing/prayers when initially confronted with illness. "